Peningkatan Kemandirian Anak Menjalankan Protokol Kesehatan Dalam Rangka Pencegahan Penyakit Menular Pada Anak-Anak Berkebutuhan Khusus Di Banjarmasin - Ermeisi Er Unja; Aulia Rachman; Gertrudis Tutpai; Lucia Andi Chrismilasari (Institut Teknologi dan Bisnis Semarang, 2023)
The independence of children with special needs in a clean and healthy lifestyle requires assistance, direction and supervision to avoid all kinds of infectious diseases that very often occur in children. One effort that can be done is to teach how to wash hands properly and properly and use masks. This community service activity is carried out in the form of counseling in the form of movements and songs about washing hands clean and how to properly use a mask, as well as watching PHBS educational videos together. The results of this community service turned out to be able to increase the knowledge of children with special needs in maintaining a clean and healthy lifestyle. There is a difference in knowledge before counseling and after counseling. After being given counseling, children can demonstrate again how to wash their hands with soap in the correct steps and use a good mask.